AVAILABILITY MANAGEMENT PLAN FOR IT SERVICE ON PPTI STIKOM SURABAYA USING ITIL V3 - Pratama, Rizki Cahyo Aji; Sutomo, Erwin; Slamet, Slamet (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Development and Application of Information Technology (PPTI) is part of Stikom Surabaya which has an important role in ensuring the course of Systems and Information Technology (STI) for each faculty. Complaints are facing is the PPTI still do not have a mechanism to manage the availability of what services they have to provide and improve. This led to the identification and measurement of actual availability of IT services in Surabaya Stikom PPTI be less than the maximum in the availability of supporting factors such as reliability, ease of maintenance, and ease of repair. To overcome these problems and increase availability in this study the use availability management of ITIL v3. In ITIL provided the best guide how to manage and improve the performance of the service. The process is done is part of the reactive and proactive activities activities. From the thesis made, documents produced in the form of document availability management along with policies, standards, and procedures for recovery for availability.